2019
DOI: 10.1037/bul0000196
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-term efficacy of executive functions cognitive training in older adults: A systematic review and meta-analysis.

Abstract: , G. (2019). Immediate and long-term efficacy of executive functions cognitive training in older adults: A systematic review and meta-analysis. Psychological Bulletin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
83
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 109 publications
(231 reference statements)
13
83
1
2
Order By: Relevance
“…Further, a large body of evidence support the notion that computerized cognitive training programmes lead to improvements in trained cognitive domains, with some findings suggesting transfer to untrained domains (e.g. [27,28]). Although speculative, computer use may be linked to cognition through an increased exposure to novelty (e.g.…”
Section: Figure 2 Mid-life Sports Club and Gym Attendance Was Associmentioning
confidence: 97%
“…Further, a large body of evidence support the notion that computerized cognitive training programmes lead to improvements in trained cognitive domains, with some findings suggesting transfer to untrained domains (e.g. [27,28]). Although speculative, computer use may be linked to cognition through an increased exposure to novelty (e.g.…”
Section: Figure 2 Mid-life Sports Club and Gym Attendance Was Associmentioning
confidence: 97%
“…16 A more recent meta-analysis assessing immediate and long-term effects of CCT on cognition and executive functions determined large improvements in trained cognitive domains related to executive functions following CCT, whereas small near-transfer (i.e., effects on untrained tasks from same trained domain) and far-transfer (i.e., effects on untrained tasks from untrained cognitive domains) outcomes. 18 A lack of clinical guidelines and standardized treatment protocols may limit the potential for a broader implementa-tion of these solutions, 19 along with the need for further studies to include functional and quality-of-life measures to assess whether gains of training extend beyond cognitive functioning to everyday life. 9 In this study, we wanted to combine the benefits of approaches based on cognitive training (i.e., standard systematic training) with those of cognitive stimulation (i.e., group training while promoting socialization and overall adjustment) in a mixed-multidomain CCT approach consisting in VR.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted the bene cial effects of CCT in older adults (25)(26)(27)(28). A recent review showed that CCT improved cognitive function of adults who are cognitively intact or mildly impaired (29).…”
Section: Discussionmentioning
confidence: 99%